2019
DOI: 10.3390/w11122594
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Water Level in the Yangtze River in Response to Natural and Anthropogenic Changes

Abstract: The water level in the Yangtze River has significantly changed due to the effects of varied precipitation and dam operations, which have exerted significant effects on irrigation, navigation, and ecosystems. Based on the measured data and the proposed calculation method, we analyzed the adjustment mechanisms of the seasonal water level in the whole Yangtze River. The results were as follows. During the dry season, the rising precipitation and dam operation both increased the water level in the upper reaches an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Water levels in many lakes and reservoirs are changing due to altered climate and water management practices (Kraemer et al., 2020; Wada et al., 2014; Ye et al., 2017). While global climate change is driving a general trend of decreasing water levels in lakes and reservoirs (Fergus et al., 2022; Yao et al., 2023), local human activities also cause water level changes over multiple timescales (e.g., Furey et al., 2004; Hannoun & Tietjen, 2023; Liu et al., 2019; Rimmer et al., 2011). In particular, many human‐made reservoirs experience large water level fluctuations on daily to annual timescales due to management for flood control, hydropower, fish passage, irrigation, and drinking water provision (Fergus et al., 2022; Hamilton et al., 2022; Jiang et al., 2018; Keller et al., 2021; Wada et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Water levels in many lakes and reservoirs are changing due to altered climate and water management practices (Kraemer et al., 2020; Wada et al., 2014; Ye et al., 2017). While global climate change is driving a general trend of decreasing water levels in lakes and reservoirs (Fergus et al., 2022; Yao et al., 2023), local human activities also cause water level changes over multiple timescales (e.g., Furey et al., 2004; Hannoun & Tietjen, 2023; Liu et al., 2019; Rimmer et al., 2011). In particular, many human‐made reservoirs experience large water level fluctuations on daily to annual timescales due to management for flood control, hydropower, fish passage, irrigation, and drinking water provision (Fergus et al., 2022; Hamilton et al., 2022; Jiang et al., 2018; Keller et al., 2021; Wada et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Water levels in many lakes and reservoirs are changing due to altered climate and water management practices (Kraemer et al, 2020;Wada et al, 2014;Ye et al, 2017). While global climate change is driving a general trend of decreasing water levels in lakes and reservoirs (Fergus et al, 2022;Yao et al, 2023), local human activities also cause water level changes over multiple timescales (e.g., Furey et al, 2004;Hannoun & Tietjen, 2023;Liu et al, 2019;Rimmer et al, 2011). In particular, many human-made reservoirs experience large water level manuscript submitted to JGR Biogeosciences 3 fluctuations on daily to annual timescales due to management for flood control, hydropower, fish passage, irrigation, and drinking water provision (Fergus et al, 2022;Jiang et al, 2018;Keller et al, 2021;Wada et al, 2014;Hamilton et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The water level has become a crucial proxy parameter for monitoring anthropogenic and climate change effects on water resources in an area. For instance, the monitoring of the changes of the water level in the Yangtze River has shown that there has been a meaningful change due to the effects of various rainfall and dam operations, which have significantly affected irrigation, navigation, and the ecosystem, while also providing information related to water management and the effects of climate change by revealing the average water level trend [16]. Further, water level monitoring over the past 52 years has revealed that rainfall is the dominant factor that causes seasonal variations in water level, while the arrangement of the floodgates and dams has been the primary driver of hydrological regime change in the last 20 years.…”
Section: Introductionmentioning
confidence: 99%